COMPILATION OF ORES QUALITY PLANS USING ARTIFICIAL MAGNETIZING METHOD - PORTNOV, V.; YUROV, V.; REVA, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2006)
The outcomes of perennial researches and minings of the theory of operation of a method of simulated bias on iron-ore fields of Kasakhstan are submitted.